ATM-Mediated Stabilization of hMutL DNA Mismatch Repair Proteins Augments p53 Activation during DNA Damage - Luo, Yuhong (Mol Cell Biol, 2004)
Human DNA mismatch repair (MMR) proteins correct DNA errors and regulate cellular response to DNA damage by signaling apoptosis. Mutations of MMR genes result in genomic instability and cancer development. Nonetheless, how MMR proteins are regulated has not yet been determined. While hMLH1, hPMS2, and hMLH3 are known to participate in MMR, the function of another member of MutL-related proteins, hPMS1, remains unclear. Here we show that DNA damage induces the accumulation of hPMS1, hPMS2, and hMLH1 through ataxia-telangiectasia-mutated (ATM)-mediated protein stabilization. The subcellular localization of PMS proteins is also regulated during DNA damage, which induces nuclear localization of hPMS1 and hPMS2 in an hMLH1-dependent manner. The induced levels of hMLH1 and hPMS1 are important for the augmentation of p53 phosphorylation by ATM in response to DNA damage. These observations identify hMutL proteins as regulators of p53 response and demonstrate for the first time a function of hMLH1-hPMS1 complex in controlling the DNA damage response.